2004
DOI: 10.1007/s11661-004-0079-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modeling of quenching-induced residual stresses in the nickel-based superalloy IN718

Abstract: The residual stress fields in pieces of quenched IN718 superalloy have been characterized by neutron diffraction. The samples were in the form of cylindrical rods of length sufficient to ensure that steadystate conditions prevail at the midsection. Quenching the samples in air, water, and oil generated various residual stress fields. The interfacial heat-transfer coefficients were estimated using an inverse-modeling technique. The findings were rationalized with an elastic-plastic finite-element model that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 19 publications
(25 reference statements)
2
40
0
Order By: Relevance
“…In other words, using a strain hardening model and ignoring rate dependency at all temperatures is sufficient when computing the as-cast residual stresses. This result is consistent with both the findings of Bru et al, [34] who showed that the residual stresses in welding are mainly affected by the low-temperature mechanical properties, as well as the findings of Dye et al, [35] who examined residual stresses in quenched Ni-based superalloys. In both previous studies, the material investigated was quenched during cooling in order to achieve the desired final mechanical properties.…”
Section: B Sensitivity Analysissupporting
confidence: 93%
“…In other words, using a strain hardening model and ignoring rate dependency at all temperatures is sufficient when computing the as-cast residual stresses. This result is consistent with both the findings of Bru et al, [34] who showed that the residual stresses in welding are mainly affected by the low-temperature mechanical properties, as well as the findings of Dye et al, [35] who examined residual stresses in quenched Ni-based superalloys. In both previous studies, the material investigated was quenched during cooling in order to achieve the desired final mechanical properties.…”
Section: B Sensitivity Analysissupporting
confidence: 93%
“…The measured thermo-physical data (Tab. 2) are similar to the values given by Dye et al [15] For proprietary reasons the applied yielding data as well as the thermal conductivity data cannot be disclosed.…”
Section: Reviewssupporting
confidence: 80%
“…Also a variation of the value of h did not improve the predictions. A systematic variation of various input parameters of the simulation revealed that a more detailed knowledge of the heat transfer coefficient h as a function of temperature is required for improving the model in case of the thin plate [21]. The smaller thickness, leading to a faster cooling of the plate, seems to be responsible for a stronger influence of the exact function of h(T) on the predicted stress distribution.…”
Section: Resultsmentioning
confidence: 99%